Actualization of Moderate Islam in Sufism: Philosophy, Fahruddin Faiz's View - Al-Aluf, Widayatul Wilda; Zahra, Alifarose Syahda; ., Ubaidillah (Jurnal Spiritual Healing, 2023)
The development of religious moderation is influenced by philosophical tasawuf, which gives a new face to science. This study aims to explain Fahruddin Faiz's preaching in the actualization of moderate Islam. The focus of this research examines how the actualization of moderate Islam in the philosophical tasawuf of Fahruddin Faiz's view uses the method of library research (library research) a qualitative with discourse analysis. The findings in this study are that prior to the existence of philosophical tasawuf, tasawuf was still pure and had not been touched by philosophical teachings. so that in the end there was philosophical tasawuf where tasawuf was also influenced by philosophy, one proof of this is the existence of moderate tasawuf. And other findings that in Fahruddin Faiz's preaching regarding moderate Islam have several characteristics, including: tawazun (balanced), tawassut (not excessive), i'tidal (fair), tasamuh (tolerant), and i'tishad (simple). There is a strong connection with moderate tasawuf which means inter-religious tolerance that grows through the application of these characteristics. Fahruddin Faiz likens a tolerant person to the sea, because the sea is wide open, accepting anything. The sea is a symbol of relaxation, relief, and breadth.